The Effect of Brand Awareness and Endorsement on Consumer Loyalty To Chitato X Seventeen Products Among Young People in Kediri City - Setyoningrum, Nur Eka; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The aim of this study was to determine the influencebrand awarenessand endorsement on consumer loyalty to Chitato X Seventeen products among young people in Kediri City. Design/Method/Approach : The method used in this research is quantitative.Sampling technique using techniquepurposive sampling. The sample taken in this study were consumers who had purchased and bought Chitato X Seventeen products among young people in Kediri City totaling 55 respondents. This study uses classical assumption analysis techniques, multiple linear regression and hypothesis testing (t-test and F-test). Research Findings : The results of the t-test study showed that the brand awareness and endorsement variables partially had a significant effect on consumer loyalty. Based on the results of the F test, it is known that the brand awareness and endorsement variables simultaneously have a significant effect on consumer loyalty. Theoretical contribution/Originality : Increasing understanding of the relationship between brand awareness, endorsement, and consumer loyalty variables, especially in the context of brand collaboration with public figures on the Chitato X Seventeen product, can influence consumer behavior in the youth segment. Practitionel/Policy implications : This research provides companies like Chitato with insights to leveragebrand awarenessAndendorsementas a powerful tool to increase consumer loyalty. With a well-planned strategy, companies can increase competitiveness, expand market share, and create long-term relationships with consumers. Research limitations : Because in this study it is proven that there are still other variables such as price, product quality, and promotion, and others that influence purchasing decisions, this can be used as material for conducting similar further research in order to obtain better results.